Isolation Of Antioxidant Compounds Of N-Hexane Extract Of Nutmeg (Myristica Fragrans Houtt) Leaves - Binawati Ginting; Siti Hadijah; Hira Helwati (JURNAL KIMIA MULAWARMAN, 2017)
The isolation of antioxidant active compounds from n-hexane extract of nutmeg leaves (Myristica fragrans Houtt) with dipphenylpicrylhydrazyl (DPPH) has been carried out. n-Hexane extract of nutmeg leaves (0.35%) was obtained by partitioning of methanol extract (535.7 g) using n-hexane solvent. Isolation of active compound of n-hexane extract with gravitational column chromatography gradient elution of n-hexane : ethyl acetate with ratio (9 : 1) – (7 : 3) obtained 7 mixed fraction of MFHD1 - MFHD 7. MFHD 2 fraction further isolated obtained MFHD 2.1. The nutmeg n-hexane extracts and their fractions showed strong antioxidant activity with IC50 values ​​<100 ppm except MFHD 6 fraction showed for IC50 values of 114.95 ppm. The most potent antioxidant activity in MFHD 4 fraction with IC50 value of 0.729 ppm (compared with vitamin C value of IC50 7,875 ppm as positive control). The GC-MS analysis of the MFHA 2.1 fraction shows the presence of sitostenone and eucalyptol compounds, both of which have been reported to have been isolated from several different plants and have antioxidant activity.